Research on relationship between geomantic omen and housing choice in big data era. (4th June 2020) - Cheng, Lin
In order to make the optimal decision of housing choice based on geomantic omen, the modern information technology in big data era is applied to confirm the relationship between the geomantic omen and housing choice. Firstly, geomantic theory and residential district planning decision are discussed. Secondly, the big data-mining algorithm based on grey relational theory is studied. Thirdly, the big data relational analysis algorithm is put forward. Finally, three resident districts are used as example to carry out the grey relational analysis for the geomantic theory and housing choice. The results verify the effectiveness of the big data-mining algorithm, the relational degree between the geomantic culture and the residential region can be obtained based on the proposed model.